PENGENALAN MEDIA MASSA DAN PROFESI JURNALIS DI SMP KATOLIK ABDI SISWA JAKARTA BARAT - Roswita Oktavianti (Jurnal Bakti Masyarakat Indonesia, 2021)
Communication Study Programme is one of the programmes in tertiary education that generates human resources with journalist’s competencies. A journalist who works in a press company or mass media has a role as a pillar of democracy and has a responsibility to distribute information to the public. However, this role is becoming increasingly challenging due to the rise of citizen journalism in online media and social media. Internet users can now spread information to their audiences. Therefore, the community services team of the Faculty of Communication, Universitas Tarumanagara held an event of introductory communication science, particularly in terms of a journalist as a media worker and mass media. This introduction of mass media and journalism is conducted with groups of junior high school students in Abdi Siswa Catholic Junior High School, West Jakarta, Indonesia. The team as communication academia initially conveyed about communication study and mass communication as one of the main areas. Then it expanded toward several of mass media in Indonesia, journalists or media workers, and the source of news of the journalists. Besides, the team also giving an understanding and insight about how students can contribute to delivering information toward media. This community service event aims to give the understanding of mass media and journalists as media workers, based on the perspective of practitioners and academia.  The speaker was a journalist so the experienced and information relevant to the situation. The students were given a test afterwards, and it showed that students comprehend of mass media and journalist as a profession with an average score 7,37 out of 10. The introductory of journalism practice can be effective if the speaker enriches its presentation visually, using an interactive method, and it is delivered directly by the journalist or by the former journalistABSTRAK:Program Studi Ilmu Komunikasi di perguruan tinggi menciptakan lulusan yang salah satunya memiliki kompetensi sebagai seorang jurnalis. Jurnalis atau wartawan yang bekerja pada perusahaan pers atau media massa berfungsi sebagai pilar demokrasi dan memiliki tanggung jawab sebagai penyalur informasi kepada masyarakat. Namun, tugas ini menjadi semakin menantang ketika jurnalis dihadapkan pada jurnalisme warga di media online dan media sosial yang juga mampu menyalurkan informasi kepada khalayak. Oleh karena itu, tim pengabdian kepada masyarakat Fakultas Ilmu Komunikasi Universitas Tarumanagara memberikan pengenalan tentang Ilmu Komunikasi secara umum, khususnya terkait profesi jurnalis dan media massa. Pengenalan dilakukan pada siswa Sekolah Menengah Pertama Katolik Abdi Siswa I dan II, Jakarta Barat. Tim pengabdian mengenalkan Ilmu Komunikasi, lalu komunikasi massa sebagai salah satu area utama dalam komunikasi, berbagai jenis media massa, profesi jurnalis, hingga sumber-sumber berita jurnalis. Selain itu, tim pengabdian juga memberikan pemahaman tentang kontribusi siswa sekolah dalam praktik jurnalisme. Tujuan dari kegiatan pengabdian kepada masyarakat ini adalah untuk memberikan pemahaman tentang media massa dan profesi jurnalis dari praktisi sekaligus akademisi yang pernah memiliki pengalaman sebagai jurnalis. Dari hasil tes berupa pertanyaan yang diberikan setelah kegiatan, menunjukkan bahwa siswa memahami materi tentang media massa dan profesi jurnalis dengan nilai rata-rata 7,37 dari nilai maksimal 10. Pengenalan dunia jurnalistik yang dilakukan dengan cara presentasi yang diperkaya dengan visual, interaktif, dan disampaikan oleh pembicara yang memiliki pengalaman langsung sebagai jurnalis lebih dapat diterima oleh para siswa.